Effects of dietary vegetable oil on growth performance, digestive capacity, antioxidant capacity and expression of immune‐related genes in the hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂). (29th August 2020) - An, Wenqiang; Dong, Xiaohui; Tan, Beiping; Wu, Meihuan; Zhang, Shuang; Chi, Shuyan; Yang, Qihui; Liu, Hongyu; Yang, Yuanzhi
Abstract: An 8‐week feeding experiment was conducted to investigate the effects of dietary lipid sources on growth performance, digestive capacity, antioxidant capacity and expression of immune‐related genes in the hybrid grouper ( Epinephelus fuscoguttatus ♀× E. lanceolatus ♂). Five isoproteic and isolipidic experimental diets were formulated containing fish oil (FO), soybean oil (SO), linseed oil (LO), rapeseed oil (RO) and peanut oil (PO), respectively. Results showed that fish fed the FO diet had the highest weight gain and specific growth rate and the lowest feed conversion ratio. The hepatic aspartate aminotransferase and alanine transaminase activities in the FO group were significantly higher than those in the PO group ( p  < .05), and the highest total antioxidant capacity was observed in the FO group. Intestinal lipase, trypsin and amylase activities in the LO group were significantly higher than those in the FO and SO groups ( p  < .05). The mRNA expression levels of Toll‐like receptor 3, Toll‐like receptor 22 and myeloid differentiation factor 88 in the liver of the PO group were significantly elevated ( p  < .05), while the mRNA expression of pro‐inflammatory cytokines (tumour necrosis factor‐α and interleukin‐1β) in the RO group was significantly higher than that in the FO group, and the highest mRNA expression of anti‐inflammatory cytokines (interleukin‐10 and transforming growth factor‐β1) was recorded in the FO group. In summary, the FO and LO groups showed better growth performance, while the poor growth performance of the PO group could be attributed to aggravation of the inflammatory response. Finally, LO was recommended as the suitable lipid source replacement for FO.